Inspiration of marine sponges to design a structure for managing the coastal hydrodynamics and protection: numerical study - Hashempour, Masoumeh; Kolahdoozan, Morteza (Frontiers in Marine Science, 2023)
Climate changes and sediment discharge within the oceans trigger many problems, such as coastline erosion and coral reef extinction hazards. Therefore, it is crucial to control wave hydrodynamics in the desired manner to protect marine environments. To prevent the promotion of sedimentation, nature has its response. The tubular sponge is a marvelous animal. It has a perforated body and sucks nutrition and water from these perforations; then, it pumps the undigested materials out from the top outlet. In the current study, an apparatus inspired by natural tubular sponges (synthetic sponges) was designed. The computational fluid dynamics derived from the Reynolds-averaged Navier-Stokes equations and image processing technique (surfaceLIC) was deployed to study how the synthetic sponge affects the wave hydrodynamics. The results revealed that the suction of the body and outflow shielding phenomenon of one sponge reduces the wave transmission by up to ≈7%. In addition, the swing motion of the jet by wave train and effluent cloud generation causes the shear on the sponge. Therefore, the momentum exchange enhances through the water column (≈46% increase of turbulent kinetic energy). It is similar to the swing behavior of flexible vegetation. Furthermore, the surfaceLIC result revealed that the effluent cloud shape changes to a pear shape, symmetric, stretched (transition), and asymmetric by increasing the pumping discharge to 600 L/h. Observing the chute–jet phenomenon by surfaceLIC also proved the diffraction and creation of a low-velocity zone in the shadow region, which is proof of a breaking wave due to the sponge’s suction/pumping and perforated body. Consequently, it can be concluded that a synthetic sponge can act as both rigid and flexible vegetation. The synthetic sponge is anticipated to mitigate sedimentation by creating unique vortices, circulating flow, and its body shape.